Cortistatin-14 Exerts Neuroprotective Effect Against Microglial Activation, Blood-brain Barrier Disruption, and Cognitive Impairment in Sepsis-associated Encephalopathy - Qiang Wen; Qian Ding; Jinchao Wang; Yanhua Yin; Shangchen Xu; Yuanrong Ju; Hongsheng Ji; Bin Liu (Journal of Immunology Research)
Sepsis-associated encephalopathy (SAE) is a life-threatening deterioration of mental status in relation to long-term and disabling cognitive dysfunction that is common in intensive care units worldwide. Cortistatin-14 is a neuropeptide structurally resembling somastostatin, which has been proven to play a crucial role in sepsis. The present study aimed to explore the neuroprotective role of cortistatin-14 in sepsis-associated encephalopathy and its underlying mechanisms in a mouse model. A septic mice model was established using the cecal ligation and puncture (CLP) method. The novel object recognition test (NORT), open field test (OFT), elevated plus maze test (EPMT), and tail suspension test (TST) were used to explore the behavioral performance of the mice. Transmission electron microscopy was used to observe the microstructure of the blood-brain barrier (BBB). Evans Blue staining was used to examine the integrity of the BBB. Immunofluorescence was used to examine the morphology and infiltration of microglia. A multiplex cytokine bead array assay was used to determine cytokine and chemokine levels in mouse serum and brain tissues. NORT revealed that cortistatin treatment improved cognitive impairment in septic mice. OFT, EPMT, and TST indicated that cortistatin-14 relieved the anxiety-related behaviors of CLP mice. In addition, cortistatin-14 treatment decreased the levels of various inflammatory cytokines, including interleukin-1β, interleukin-6, interferon-γ, and tumor necrosis factor-α in both the serum and brain of septic mice. Cortistatin reduced sepsis-induced blood-brain barrier disruption and inhibited microglial activation after the onset of sepsis. Cortistatin exerts neuroprotective effects against SAE and cognitive dysfunction in a CLP-induced mouse model of sepsis.